Las montañas perfumadas: algunos aspectos relevantes de la Constitución de Antioquia de 1812 - Olano García, Hernán Alejandro (2023)
The author analyzes some of the relevant aspects of the state of Antioquia’s first constitution, issued in 1812. It was the third constitution issued in Colombia. It was also the second constitution with a republican perspective, even if it recognized the authority of the king, Fernando VII, under the condition of his being released from imprisonment by the French in Bayonne. The 298 sections of Antioquia’s 1812 Constitution are o rganized into 10 titles. Most of these sections are similar to those included in the Tunja Constitution of 1811, and most of them contain some of the institutions established 180 years later in Colombia’s 1991 Constitution.